Forest park Efficiency and Influencing Factors in Fujian Province – based on Dynamic Network DEA and Micro Data - Ran An, Xiujuan Huang (Forest Chemicals Review)
With the construction of China’s ecological civilization and high-quality development, improving the efficiency of China’s forest park has become an important issue. Based on the production characteristics of tourism products, the overall efficiency of forest park is divided into production efficiency and service efficiency. With the statistical data in Fujian province of China, dynamic network DEA was used to calculate the specific overall, production and service efficiency of 24 forest parks of Fujian province. Then, regression model based on panel data was constructed to assess and distinguish the causal factors of affecting the overall, production and service efficiency. Study shows that: 1) From 2011 to 2019, average score of service efficiency (0.280) was lower than the average score of production efficiency (0.508), while the service efficiency is more dispersed (St.D =0.316) than service efficiency. 2) Investment density, tour road density, urban population and location have significant impact on production efficiency. 3) Tour road density, urban population, GDP per capita, urbanization level and location have significant impact on service efficiency. 4) All the factors above have no significant impact on service efficiency. What are the factors affecting service efficiency need further research.